Music Therapy in Patients with Huntington's Disease: A Case Report - Monique CH van Bruggen-Rufi; Annemieke C Vink2; Wilco P Achterberg; Raymund AC Roos (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2017)
This paper reports about 2 patients with Huntington's disease who benefit  greatly from music therapy while they are struggling with behavioral and emotional problems, due to the advanced stage of the disease. Huntington's disease (HD) is an inherited neuropsychiatric disease with progressive neural  degeneration of the basal ganglia and gradual atrophy of the frontal and temporal cortex. Symptoms are progressive and include motor, emotional and cognitive disturbance. There is as yet no cure for HD, nor can its progress be reversed or slowed down. All treatment is aimed at improving quality of life. Music therapy is a non-pharmacological intervention to improve communication skills, reducing behavioral problems and thus leading to a better quality of life in patients with HD. There is little knowledge on how music therapy may contribute to improve the QoL in HD. This case report provides greater insight into how to treat patients with HD, especially in the advanced stage of the disease.